A Practical Guide to Lightcurve Photometry and Analysis - Warner, Brian D. (The Patrick Moore Practical Astronomy Series, 2016)
For those with access to even a modest telescope and CCD camera, this new and improved guide delivers all the information needed to take part in the scientific study of asteroids and variable stars. New techniques in photometry continue to be refined, and expert Brian Warner covers the developing territory in detail for those both new and experienced. Updated to reflect changes in telescope and CCD technology, it also includes an expanded chapter on the analysis of asteroid lightcurves to cover some of the common pitfalls that lead to incorrect answers as well as how to discover an asteroid satellite via lightcurves. With this information, amateur astronomers can use commercially available equipment to determine the rotation rate, size, and shape of asteroids. Similarly, it is possible to discover the size, temperature, and orbits of stars in binary systems by using this powerful technique. Brian Warner yet again delivers all the material needed for readers to understand the theory, and avoid the practical pitfalls of lightcurve photometry. Detailed examples are given for obtaining data, and of course for the exciting and rewarding task of analyzing the data to determine the physical properties of the objects. It also includes many detailed finder charts with magnitudes for reference and detailed steps on how to go about gathering data for specific projects without misinterpretation. Any college student or amateur astronomer who wants to go beyond mere imaging with a CCD camera and enter the challenging world of "real science" via the lightcurves of asteroids and binary stars will find everything necessary in this updated book. .